Distribution of Coronal Plane Alignment of the Knee Classification in Patients with Knee Osteoarthritis in Japan - Toyooka, Seikai; Osaki, Yutoshi; Masuda, Hironari; Arai, Noriaki; Miyamoto, Wataru; Ando, Shuji; Kawano, Hirotaka; Nakagawa, Takumi (The Journal of Knee Surgery, 2022)
Coronal plane alignment of the knee (CPAK) has recently been proposed as a simple and universal classification system to determine the suitability of a particular phenotype of the knee to a specific alignment strategy for knee replacement surgery. Although racial differences may affect knee alignment, there are no reports on the racial distribution of this classification system. We aimed to clarify the distribution of CPAK classification in patients with osteoarthritis who underwent total knee arthroplasty (TKA) in Japan. Consecutive patients who underwent primary TKA were analyzed retrospectively. The knees were categorized according to the CPAK classification system which comprised of two independent variables (arithmetic hip–knee–ankle [aHKA] angle and joint-line obliquity [JLO]) with three respective subgroups to create the following nine phenotypes of the knee: type I (varus aHKA and apex distal JLO), type II (neutral aHKA and apex distal JLO), type III (valgus aHKA and apex distal JLO), type IV (varus aHKA and neutral JLO), type V (neutral aHKA and neutral JLO), and type VI (valgus aHKA and neutral JLO), type VII (varus aHKA and apex proximal), type VIII (neutral aHKA and apex proximal), and type IX (valgus aHKA and apex proximal). The distribution of the phenotypes in the Japanese population was investigated as a primary outcome. To accurately compare the results with previous studies conducted on non-Japanese patients, a sex-matched distribution was investigated as a secondary outcome. A total of 570 knees were investigated of which 500 knees were examined after exclusions. The most common distribution was type I (53.8%), followed by type II (25.4%), type III (8.2%), type IV (7.2%), type V (4.4%), and type VI (1.0%). Types VII, VIII, and IX were not distributed. The sex-matched distribution was nearly identical to the overall distribution in Japan. The majority of patients with knee osteoarthritis in Japan had medially tilted joints with constitutional varus alignment.
Keywords: coronal plane alignment of the knee; osteoarthritis; constitutional varus; kinematic alignment; mechanical alignment